DINAMIKA POLITIK IDENTITAS DAN DINASTI DI INDONESIA: Menuju Politik yang Ideal Melalui Eksplorasi Teori Maslahah - Sugitanata, Arif; Hamdi, Muh. Rizal; Nuriskandar, Lalu Hendri; Jayadi, Nurman (PRODI HUKUM TATANEGARA, 2022)
This research aims to explore the dynamics of identity politics and dynasties in Indonesia and efforts to present ideal politics. This study uses a literature review, adopts a qualitative research approach, and applies descriptive analysis techniques based on Maslahah's theory. The results show that identity politics and dynasties play a significant role in the formation of power, often relying on ethnic, religious, or family identity to mobilise support, which can increase the representation of certain groups but also trigger polarisation and erode the principles of democracy and meritocracy. The interaction between identity politics and dynasties creates complexities in political dynamics that can hinder the achievement of an ideal politics based on democracy, justice and equality. On the other hand, efforts towards ideal politics in Indonesia must involve a strong commitment to the principles of democracy, justice and equality, strengthening the foundations of inclusive and participatory democracy, ensuring free and fair elections, and building political awareness and political education among the people. Eradicating corruption, collusion, and nepotism is also a top priority in creating clean politics and integrity. In addition, nurturing diversity and pluralism is an essential step in creating a more inclusive and democratic society. A Maslahah theory-based analysis also emphasises the achievement of the common good and the prevention of harm, which are essential in guiding Indonesia towards ideal politics. It includes empowering individuals and groups in society, promoting social justice, and maintaining social harmony. As such, this study makes an essential contribution to the understanding of identity and dynastic politics in Indonesia and the steps needed to achieve a more equitable and inclusive politics.